2019
DOI: 10.1155/2019/6198368
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Trauma-Related Eviscerations: Analysis of 821 Cases

Abstract: Evisceration is the end therapeutic approach for the treatment of severe ocular trauma cases, and it is a tremendous loss for patients. In this study, we explored the changing trends in the number of surgeries performed, demographic data and ocular features, and risks for early evisceration, aiming to provide more data for the additional prevention and management strategies for this catastrophic problem. This was a retrospective study that included patients who underwent ocular evisceration at the Zhongshan Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…However, in the case of total corneal melting, the rate of evisceration increased to 35.4%, consistent with the current findings (32). We previously identified IOFB as an important risk factor for endophthalmitis and endophthalmitis as a significant factor for eviscerations (11)(12)(13)(14). Together, these results suggest that total corneal melting, NLP, and IOFB are risk factors for evisceration in patients with OC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in the case of total corneal melting, the rate of evisceration increased to 35.4%, consistent with the current findings (32). We previously identified IOFB as an important risk factor for endophthalmitis and endophthalmitis as a significant factor for eviscerations (11)(12)(13)(14). Together, these results suggest that total corneal melting, NLP, and IOFB are risk factors for evisceration in patients with OC.…”
Section: Discussionsupporting
confidence: 90%
“…We previously identified ocular trauma and intraocular foreign bodies (IOFB) as important risk factors for endophthalmitis (11,12) and summarized the microbiological isolates and antibiotic susceptibilities of culture-proven endophthalmitis (13,14). In the present study, we reviewed the data of patients hospitalized with OC in the past 10 years to (1) describe the clinical characteristics of OC, (2) explore the microbiological isolates of OC, and (3) identify the risk factors related to NLP and evisceration in patients with OC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the traumatic cause was not the main cause in our study with 38.1% of cases, this percentage is similar to that found in Jordan with 33.3% 5 and Saudi Arabia with 34.5% 2 ; higher than in Mexico with 22.2% 7 but lower than the Colombian study with 51% 10 , Turkey 60.1% 4 , and China with 67% 6 . In general, traumatic causes related to accidents at work patients; however, in our study, most of the patients reported not having an occupation or belonging to the informal economy, which draws attention and opens the need to delve into the possible reasons for the trauma and would explain in part the predominance of the pathological cause.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the causes that lead to evisceration of the eye, studies conducted in countries such as Turkey, China, and Jordan found that the main reason is trauma, representing 40% of the cases [4][5][6] . On the other hand, in investigations carried out in Mexico, the United States of America, Iran, and Saudi Arabia, the most frequent causes are non-traumatic, among which endophthalmitis and painful blind eye stand out 2,7,8 .…”
Section: Introductionmentioning
confidence: 99%